Attachment Patterns Of Fish Traders In Traditional Markets Nangggalo District, Padang City - Irwan, Irwan; Zusmelia, Zusmelia; Elvawati, Elvawati; Melia, Yeni; Jannah, Latifah Izzatul; Lubis, Geby Cahyani (CV. AFDIFAL MAJU BERKAH, 2024)
Traditional markets do not look at caste, buyers can mix well with sellers without any restrictions. The buying and selling system occurs by mutual action of buyers and sellers. In traditional markets, the relationship between traders and buyers is not just the seller receiving money and the buyer receiving goods, but can form social relationships that exist in the buying and selling process. The focus of this study is to analyze the Attachment Pattern of Fish Traders in the Traditional Market, Nanggalo District, Padang City. This study uses a qualitative approach that takes a descriptive type. Purposive sampling was used to select research informants. Research informants are attachments between fish traders. The data collection method begins through in-depth interviews, observations and document data collection. The unit of analysis is carried out from several stages, one of which is data collection, data reduction, data analysis and drawing conclusions which are referred to in the Miles and Huberman model. The results of this study show that the existence of fish traders in traditional markets is inseparable from the cooperation between traders in the process of taking fish. This is marked by the relationship that occurs between large actors such as large agents to small agents as well as to traders where a network has been established, which in turn forms attachment between traders which is characterized by trust in providing merchandise at the initial stage with a system that is no longer the same at the beginning. know, but already at the stage of being able to take fish first with the system of being allowed to owe and the installment system.